Teacher’s Perception of Literacy Program: Its Implication to Their Attitudes and Actions - Susanto, Fajar; Rifai, Irfan (Universitas PGRI Adi Buana Surabaya, 2018)
Teachers as the tip of lance play important roles in the success of the implementation of school literacy program such as possessing positive perception of literacy practices. Recognizing the important roles of teachers in the implementation of literacy program in the schools, this study aims to investigate the teachers‟ perception toward the implementation of literacy program at a Junior High School in Surabaya. This study is designed as an interpretative qualitative approach. Primary data were obtained through open interviews and observations and supplementary data source included student journal. The data findings showed that teachers have positive perceptions on literacy program. They argue that school literacy program potentially enables to build up the students‟ good habits. Through the habituation of a thirty-minute reading before the class, it can raise the students‟ awareness on literacy - reading and writing. Moreover, the school literacy program benefits the students‟ competency in understanding long texts and can help them to be more critical and creative. In addition, instead of students who take advantageous from the literacy program, teachers are also equally benefited from exposure to daily literacy practices within the school. The teachers tend to follow the rhymes of the literacy practices which are marked by reading and writing activities. In this sense, literacy practices facilitate teachers to develop their practical writing abilities and increase their awareness to be the role model in the classrooms particularly in the literacy practices. This study emphasizes that literacy practices can be double blades, on one side it is beneficial for the students and on another side it is advantageous for the teachers